Accessory and Expiratory Muscles Activation During Spontaneous Breathing Trial: A Physiological Study by Surface Electromyography - Pozzi, Matteo; Rezoagli, Emanuele; Bronco, Alfio; Rabboni, Francesca; Grasselli, Giacomo; Foti, Giuseppe; Bellani, Giacomo (Frontiers in Medicine, 2022)
Background The physiological and prognostical significance of accessory and expiratory muscles activation is unknown during a spontaneous breathing trial (SBT). We hypothesized that, in patients experiencing weaning failure, accessory and expiratory muscles are activated to cope with an increased respiratory workload. Purpose To describe accessory and expiratory muscle activation non-invasively by surface electromyography (sEMG) during an SBT and to assess differences in electrical activity (EA) of the inspiratory and expiratory muscles in successful vs. failing weaning patients. Methods Intubated patients on mechanical ventilation for more than 48 h undergoing an SBT were enrolled in a medical and surgical third-level ICU of the University Teaching Hospital. Baseline characteristics and physiological variables were recorded in a crossover physiologic prospective clinical study. Results Of 37 critically ill mechanically ventilated patients, 29 (78%) patients successfully passed the SBT. Rapid shallow breathing index (RSBI) was higher in patients who failed SBT compared with the successfully weaned patients at baseline and over time (group-by-time interaction p < 0.001). EA of both the diaphragm (EAdisurf) and of accessory muscles (ACCsurf) was higher in failure patients compared with success (group-by-time interaction p = 0.0174 and p < 0.001, respectively). EA of expiratory muscles (ESPsurf) during SBT increased more in failure than in weaned patients (group-by-time interaction p < 0.0001). Conclusion Non-invasive respiratory muscle monitoring by sEMG was feasible during SBT. Respiratory muscles EA increased during SBT, regardless of SBT outcome, and patients who failed the SBT had a higher increase of all the inspiratory muscles EA compared with the patients who passed the SBT. Recruitment of expiratory muscles—as quantified by sEMG—is associated with SBT failure.